Teologi Sapaan: Pelayanan Non-Verbal sebagai Pewartaan Firman Tuhan di Gereja Kontemporer - Tiopan Aruan (Sekolah Tinggi Teologi Tawangmangu, 2026)
This research is motivated by the tendency of the contemporary church to identify ministry primarily with pulpit activities and verbal proclamation, thus neglecting non-verbal expressions such as greetings, smiles, and interpersonal presence. Several studies on Christian hospitality have emphasized ethical and communal aspects, but have not specifically examined non-verbal ministry as a form of evangelism within a practical theological framework. The method used is a qualitative-descriptive approach through literature studies, with practical theology as an interpretive framework for understanding church practices as a locus of theological reflection. This research aims to build a theological understanding of non-verbal ministry as an integral part of evangelism in the contemporary church. The results show that non-verbal ministry, such as friendly greetings and church hospitality, is not merely a form of social ethics, but a theological action that concretely communicates God's love in interpersonal relationships. Furthermore, this form of ministry serves as the starting point for faith encounters, where individuals first experience the presence of the church and the Gospel message, even before hearing the verbal proclamation.AbstrakPenelitian ini dilatarbelakangi oleh kecenderungan gereja kontemporer yang mengidentikkan pelayanan terutama dengan aktivitas mimbar dan pewartaan verbal, sehingga mengabaikan ekspresi non-verbal seperti sapaan, senyuman, dan kehadiran interpersonal. Sejumlah studi mengenai hospitalitas Kristen telah menekankan aspek etis dan komunal, namun belum secara khusus mengkaji pelayanan non-verbal sebagai bentuk pewartaan Injil dalam kerangka teologi praktis. Metode yang digunakan adalah pendekatan kualitatif-deskriptif melalui studi literatur, dengan teologi praktis sebagai kerangka interpretatif untuk memahami praktik gerejawi sebagai lokus refleksi teologis. Penelitian ini bertujuan untuk membangun pemahaman teologis mengenai pelayanan non-verbal sebagai bagian integral dari pewartaan Injil dalam gereja kontemporer. Hasil penelitian menunjukkan bahwa pelayanan non-verbal, seperti sapaan yang ramah dan hospitalitas gerejawi, bukan sekadar bentuk etika sosial, melainkan tindakan teologis yang secara konkret mengomunikasikan kasih Allah dalam relasi antarpribadi. Lebih lanjut, bentuk pelayanan ini berfungsi sebagai titik awal perjumpaan iman, di mana individu pertama kali mengalami kehadiran gereja dan pesan Injil, bahkan sebelum mendengar pewartaan verbal.